RELATIONS OF AR-RAZI TO THE AFFECTS OF THE SOUL (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In the concept of Ar-Razi, personality is created through personal rational and spiritual perfection. A perfect personality is a personality that is aware of its spectacularity and the flaws of the soul. Therefore, a person must eliminate such obstacles from his life as worldly lust, vanity, envy, etc. He is prescribed to purify himself and discard what vices push him to. Abstinence means chastity, moderation and patience. In other words, Ar-Razi sees the main attitudes of personality in getting rid of greed, the desire to rule, vanity, arrogance, etc. To get rid of these vices, a person "should not consider himself so important and great in his soul as to show himself in the eyes of others as superior in something to his equals, but also not to belittle his dignity and not to humiliate himself in order to look in the eyes of others below them and other people like himself. If he does exactly this and corrects his soul, he will get rid of arrogant and vile humiliation. And then people will call him a man who knows his own worth" [1, 47].